DETERMINAN YANG MEMPENGARUHI DISPARITAS ANTAR WILAYAH DI KAWASAN TIMUR INDONESIA TAHUN 2014-2019 - Salsabillah, Hurriyah; Bahtiar Fitanto (Journal of Development Economic and Social Studies, 2024)
Significant developmental disparity between the Western Indonesian Region (KBI)  and the Eastern Indonesian Region (KTI), evident in dominance of provinces in Java and Sumatra, has emerged as a persistent concern. The KBI has consistently contributed over 80% to the total Gross Domestic Product (GDP) over the past three decades. This research aims to conduct a comprehensive examination of the factors contributing to regional disparities in the Eastern Indonesian Region. Employing panel data, the study utilizes regression to analyze the correlation between variables such as the Open Unemployment Rate (TPT), investment, Regional Gross Domestic Product (PDRB), education, and regional expenditures on regional disparities in the Eastern Indonesian Region. This research used secondary data sourced from Badan Pusat Statistik (BPS) spanning from 2014 to 2019 period using documentation method. This study results on PDRB has a positive and significant impact, while education and regional expenditures have negative and significantly correlated with disparities among regions. However, the other two variables, namely investment and TPT are not show significant partial impacts.